Interpersonal sensorimotor communication shapes intrapersonal coordination in a musical ensemble - Laroche, Julien; Tomassini, Alice; Volpe, Gualtiero; Camurri, Antonio; Fadiga, Luciano; D’Ausilio, Alessandro (Frontiers in Human Neuroscience, 2022)
Social behaviors rely on the coordination of multiple effectors within one’s own body as well as between the interacting bodies. However, little is known about how coupling at the interpersonal level impacts coordination among body parts at the intrapersonal level, especially in ecological, complex, situations. Here, we perturbed interpersonal sensorimotor communication in violin players of an orchestra and investigated how this impacted musicians’ intrapersonal movements coordination. More precisely, first section violinists were asked to turn their back to the conductor and to face the second section of violinists, who still faced the conductor. Motion capture of head and bow kinematics showed that altering the usual interpersonal coupling scheme increased intrapersonal coordination. Our perturbation also induced smaller yet more complex head movements, which spanned multiple, faster timescales that closely matched the metrical levels of the musical score. Importantly, perturbation differentially increased intrapersonal coordination across these timescales. We interpret this behavioral shift as a sensorimotor strategy that exploits periodical movements to effectively tune sensory processing in time and allows coping with the disruption in the interpersonal coupling scheme. As such, head movements, which are usually deemed to fulfill communicative functions, can thus be adapted to help regulate own performance in time.